Analysis of marketing strategies for sea milkfish shredding at dapor sehati micro business - Moh. Rasidi; Ramli Ramli; Syamsul Arifin; Taufiqur Rohman (Trigin Publisher, 2023)
Currently, sales of shredded sea milkfish produced by Dapor Sehati have not met sales targets, therefore an appropriate marketing strategy needs to be formulated. Research on marketing strategies for fish shredded has been carried out a lot, however, not all of these strategy formulations can be applied, therefore it is necessary to carry out research on the formulation of appropriate marketing strategies for sea milkfish shredded in the Dapor Sehati micro business. This research aims to increase the sales results of sea milkfish Shredding produced by the Dapor Sehati micro business through formulating appropriate marketing strategies. The method used to formulate a marketing strategy is SWOT analysis and QSPM. The research results show that marketing alternative strategies for sea milkfish shredded based on a priority scale are (1) Increasing the marketing human resources capacity, (2) Improving product quality and packaging to obtain consumer satisfaction, (3) Conducting market research periodically to adapt to consumer dynamics, (4) Building the right product brand awareness to win the competition, (5) Optimizing excellent service to increase the quantity and quality of the marketing network, and (6) Optimizing cooperation with the raw material supplier network to overcome fluctuations in raw material prices